Rapid and accurate liquid chromatography and tandem mass spectrometry method for the simultaneous quantification of ten metabolic reactions catalyzed by hepatic cytochrome P450 enzymes. Issue 19 (7th September 2015) - Shi, Rong; Ma, Bingliang; Wu, Jiasheng; Wang, Tianming; Ma, Yueming
<x xml:space="preserve">Abstract</x> The hepatic cytochrome P450 enzymes play a central role in the biotransformation of endogenous and exogenous substances. A sensitive high‐throughput liquid chromatography with tandem mass spectrometry assay was developed and validated for the simultaneous quantification of the products of ten metabolic reactions catalyzed by hepatic cytochrome P450 enzymes. After the substrates were incubated separately, the samples were pooled and analyzed by liquid chromatography with tandem mass spectrometry using an electrospray ionization source in the positive and negative ion modes. The method exhibited linearity over a broad concentration range, insensitivity to matrix effects, and high accuracy, precision, and stability. The novel method was successfully applied to study the kinetics of phenacetin‐O deethylation, coumarin‐7 hydroxylation, bupropion hydroxylation, taxol‐6 hydroxylation, omeprazole‐5 hydroxylation, dextromethorphan‐O demethylation, tolbutamide‐4 hydroxylation, chlorzoxazone‐6 hydroxylation, testosterone‐6β hydroxylation, and midazolam‐1 hydroxylation in rat liver microsomes.